Cardiac Fibroblasts and Cardiac Fibrosis: Precise Role of Exosomes - Ranjan, Prabhat; Kumari, Rajesh; Verma, Suresh Kumar (Frontiers in Cell and Developmental Biology, 2019)
Exosomes are a group of extracellular microvesicles that deliver biologically active RNAs, proteins, lipids and other signalling molecules to recipient cells. Classically, exosomes act as a vehicle by which cells or organs communicate with each other to maintain cellular/tissue homeostasis and to respond to pathological stress. Most multicellular systems, including the cardiovascular system, use exosomes for intercellular communication. In heart, endogenous exosomes from cardiac cells or stem cells aid in regulation of cell survival, cell proliferation and cell death; and thus tightly regulate cardiac biology and repair processes. Pathological stimulus in heart alters secretion and molecular composition of exosomes, thus influencing the above processes. The past decade has yielded increasing interest in the role of exosomes in the cardiovascular system and significant contribution of cardiac fibroblast and mediated cardiac fibrosis in heart failure, in this review we had overviewed the relevant literatures about fibroblast exosomes, its effect in the cardiovascular biology and its impact on cardiovascular disease. This review briefly describes the communication between fibroblasts and other cardiac cells via exosomes, the influence of such on myocardial fibrosis and remodelling, and the possibilities to use exosomes as biomarkers for acute and chronic heart disease.